Neuromodulation of Electrically Induced Hyperalgesia in the Trigeminocervical System - Reindl, Caroline; Seifert, Frank; Nickel, Franziska; Maihoefner, Christian (Pain Practice, 2016)
Trigeminal and cervical afferents converge on neurons of the trigeminocervical complex and may significantly alter the function of these neurons. This interaction may have implications for the pathophysiology and treatment of primary headache disorders. Therefore, the aim of this work was to study pain modulatory mechanisms within the trigeminocervical complex.We used an electrical pain model challenging pro- and antinociceptive systems in 19 healthy volunteers.Transcutaneous supraorbital noxious electrical low-frequency stimulation (0.5 Hz), known to induce both hyperalgesia due to central sensitization (as a marker of pain facilitation) and habituation (as a marker of pain inhibition), was combined with different noxious stimulation paradigms applied to the innervation territory of upper cervical afferents. We investigated the effects of concurrent stimulation in the cervical/extratrigeminal system on habituation profiles, hyperalgesic area, pain, and detection thresholds in the trigeminal system.It was previously shown that conditioning 20-Hz noxious electrical stimuli may provoke centrally mediated sensory decline that possesses heterotopic antihyperalgesic properties. Occipital and forearm costimulation at a frequency of 20 Hz had no significant modulating effect on supraorbital pain adaptation, hyperalgesic area, or pain perception. Effects for trigeminal stimulation were independent of occipital stimulus intensity. Furthermore, for single occipital stimulation at 0.5 and 20 Hz, no somatosensory changes could be demonstrated within the trigeminal system.Trigeminal nociception stayed unchanged despite of occipital costimulation.
EVALuna2:22473